'Jhuming' (Shifting Cultivation) in Mizoram (India) and New Land Use Policy - how Far it has Succerded in Containing This Primitive Agriculture Practice - Garbyal, S. S. (Indian Forester, 1999)
Shifting cultivation that is known as 'jhuming' in Mizoram, is an integral part of the sociocultural life of Mizos. With increase in population the jhuming cycle has shortened considerably and the productivity ofland has fallen with devastating impact on the environment. The Govt. ofMizoram in 1984 launched a programme called New Land Use Policy (NLUP) with an objective to put an end to the practice of jhuming by providing alternative land based permanent occupation and stable income to the families practicing jhuming (jhumias) in rural areas thereby raising their standard of living. Assistance is provided for various trades or occupation for a period of three years. The programme is operated on yearly basis. In addition to the main trade, assistance is also provided for subsidiary trades so that the beneficiary earns income throughout the year. It is, however, found that the NLUP have not had any impact on jhuming as most of the beneficiaries are continuing jhuming even after receiving assistance under NLUP. Programme has also failed to bring out any perceptible improvement in the economic condition of the villagers. There has not been any significant change in the quality oftife of the beneficiaries. There is a need to bring out changes in the attitudes towards Jhuming. The programme needs restructuring. The beneficiaries, village councils and YMA need to be involved at all levels, proper marketing facilities for the products are required to be provided, utmost care is required while selecting the beneficiaries, the resources of various participating departments are required to be pooled in and effective monitoring and evaluation system needs to be put in place.